Investigating the esl teachers’ and students’ attitude towards the use of computer in english language classroom - Abdul Razak, Noor Zainab; Eswaran, Jeyavany (2010)
The purpose of this study is to investigate teachers and students attitude and motivation towards the use of computer in an ESL classroom. The respondents in this study are six English language teachers and thirty form two students from one of the rural school in Kota Tinggi district. The methodology used in this study is two sets of questionnaire. The data in this study have been analyzed using SPSS 12.0 software (Statistical Packages for Social Science) and presented in the form of frequency and percentage. The findings of this study illustrate that most of the teachers and students have a positive attitude towards the use of computer in an ESL classroom. Also, this study proves that students have high motivation when computers are used in an ESL classroom. Through this study, it could be concluded that the use of computer in an ESL classroom should be encouraged because it helps to motivate students and generate a positive attitude towards English language learning.